VÓRTICES NA REDUÇÃO DIMENSIONAL DO MODELO DE MAXWELL-CARROLL-FIELD-JACKIW-HIGGS - Neves, Alyson Bruno Fonseca (2012)
This monograph presents the study of vortices BPS in a model obtained by dimensional reduction of the (1+3)−D Maxwell-Carroll-Field-Jackiw-Higgs s electrodynamics to (1+2)−D. The Maxwell-Carroll-Field-Jackiw-Higgs model is defined by the following Lagrangian density L1+3 = −14FμνFμν −14 ϵμνκλ (kAF )μ AνFκλ + |Dμϕ|2 − V (|ϕ|), the first two terms constitute the CPT-odd electrodynamics of the standard model extension (SME). The term ϵμνκλ (kAF )μ AνFκλ is called the Carroll-Field-Jackiw s term. The dimensional reduction of this model is given by the following Lagrangian density L1+2 = − 14FμνFμν +s4 ϵμνκAμFνκ +12∂μψ∂μψ −12ϵμνκ (kAF )μ ψ∂νAκ−12 ϵμκν (kAF )μ Aκ∂νψ + |Dμϕ|2 − e2ψ2 |ϕ|2 − V (|ϕ|2 , ψ), it is observed that if (kAF )μ = 0 we obtain the Maxwell-Chern-Simons-Higgs (MCSH) model. This way, our planar model is a MCSH model modified by an interaction between the gauge field Aμ and the neutral scalar field ψ whose coupling constant is (kAF )μ, the Lorentz-violating vector field background. The existence of stable BPS v´ortices implies in a null (kAF )0 component. The study shows that the influence of the Lorentz violation is clearly manifested when the vortex s winding number is greater than 1.